1992
DOI: 10.1002/asna.2113130502
|View full text |Cite
|
Sign up to set email alerts
|

Lymanα forests and the evolution of the universe

Abstract: The Lya forest absorption lines in the spectra of quasars are interpreted as caused by the crossings of the light beam with the walls of a bubble structure (expanding with the Hubble flow only). Then, the typical separation between the absorption lines is proportional to the mean size of the bubbles. The variable factor is the expansion rate H [ z ] . T h e Friedmann regression analysis of the observed line separations determines the density parameter 0 0 and the normalized cosmological term A0 = A c 2 / 3 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…While there are a number of ways to account for this in ΛCDM models (e.g., by "tilting" the primordial spectrum), the data are fit most naturally by a "no-CDM" ΛBDM model with Ω cdm = 0, Ω m,0 = Ω bar and Ω Λ,0 ≈ 1 [142]. Models of this kind have been discussed for some time in connection with analyses of the Lyman-α forest of quasar absorption lines [50,143]. The Wmap data show a stronger second peak and are fit by both ΛCDM and ΛBDM-type models [144].…”
Section: Cosmological Concordancementioning
confidence: 99%
See 1 more Smart Citation
“…While there are a number of ways to account for this in ΛCDM models (e.g., by "tilting" the primordial spectrum), the data are fit most naturally by a "no-CDM" ΛBDM model with Ω cdm = 0, Ω m,0 = Ω bar and Ω Λ,0 ≈ 1 [142]. Models of this kind have been discussed for some time in connection with analyses of the Lyman-α forest of quasar absorption lines [50,143]. The Wmap data show a stronger second peak and are fit by both ΛCDM and ΛBDM-type models [144].…”
Section: Cosmological Concordancementioning
confidence: 99%
“…Fig. 23(a) shows the spectral intensity of background radiation from vacuum decay under our standard assumptions, including the relativistic definition (136) of vacuum luminosity and the values of Ω r,0 and β given by (143) and (144) respectively. Five groups of curves are shown, corresponding to values of x m between 3 × 10 −5 and the theoretical maximum of 0.25.…”
Section: The Microwave Backgroundmentioning
confidence: 99%
“…Their best-fit model, which came to be known as the "Bonn-Potsdam" or BN-P model, was characterized by a dark-energy density of Ω Λ,0 ≈ 1.08 and a total matter density of Ω M,0 ≈ 0.014, as measured in units of the critical density [88][89][90][91][92][93].…”
Section: The Bonn-potsdam Modelmentioning
confidence: 99%
“…55. Here, it was reported that, even as early as the 1940's, Pontecorvo and Alvarez independently proposed that the neutrinos produced in the solar interior might be detectable on earth by neutrino capture in 37 Cl. This idea was revived by Fowler, Cameron, Davis, and Bahcall after it became clear that there was a good chance that 8 B solar neutrinos might be more intense than previously seemed likely.…”
Section: Solar Neutrinosmentioning
confidence: 93%
“…Note, however, that this conclusion is not necessarily true if the cosmological constant , which is usually set to zero, has a finite value as recently proposed. (37) Although the standard model provides a consistent picture of the nuclear ashes of the early universe, this is not sufficient to establish the correctness of the model or its uniqueness. Thus it seems to be advisable to investigate alternative models in which one or even several of the assumptions made in the standard model are relaxed.…”
Section: Nucleosynthesis In the Standard Big Bang Modelmentioning
confidence: 98%